Stroke Prevention in Atrial Fibrillation: Focus on Latin America - Massaro,Ayrton R. (2016)
Abstract Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, with an estimated prevalence of 1-2% in North America and Europe. The increased prevalence of AF in Latin America is associated with an ageing general population, along with poor control of key risk factors, including hypertension. As a result, stroke prevalence and associated mortality have increased dramatically in the region. Therefore, the need for effective anticoagulation strategies in Latin America is clear. The aim of this review is to provide a contemporary overview of anticoagulants for stroke prevention. The use of vitamin K antagonists (VKAs, eg, warfarin) and aspirin in the prevention of stroke in patients with AF in Latin America remains common, although around one fifth of all AF patients receive no anticoagulation. Warfarin use is complicated by a lack of access to effective monitoring services coupled with an unpredictable pharmacokinetic profile. The overuse of aspirin is associated with significant bleeding risks and reduced efficacy for stroke prevention in this patient group. The non-VKA oral anticoagulants (NOACbs) represent a potential means of overcoming many limitations associated with VKA and aspirin use, including a reduction in the need for monitoring and a reduced risk of hemorrhagic events. The ultimate decision of which anticoagulant drug to utilize in AF patients depends on a multitude of factors. More research is needed to appreciate the impact of these factors in the Latin American population and thereby reduce the burden of AF-associated stroke in this region.